Cancer Informatics 2022: Real-World Data Yields Important Insights into the Conduct of Clinical Trials and Registries - Warner, Jeremy L.; Rooney, Michael K.; Patt, Debra (Yearbook of Medical Informatics, 2022)
Objective: To summarize significant research contributions on cancer informatics published in 2021.Methods: An extensive search using PubMed/MEDLINE and Altmetric scores was conducted to identify the scientific contributions published in 2021 that address topics in cancer informatics. The selection process comprised three steps: (i) 15 candidate best papers were first selected by the two section editors, (ii) external reviewers from internationally renowned research teams reviewed each candidate best paper, and (iii) the final selection of two best papers was conducted by the editorial board of the IMIA Yearbook.Results: The two selected best papers demonstrate some of the promises and shortcomings of real-world data.Conclusion: Cancer informatics is a maturing subfield of biomedical informatics. Applications of informatics methods to real-world data are especially notable in 2021.
Keywords: Neoplasms; informatics; health information technology; disparities